Statements journalism: When the press renounces being the scene of facts - Munive, Mario (2016)
It is not a journalism genre, but a discourse that seems to be in the DNA of Latin America’s press. On the newsroom it is known as “He said, she said” journalism. This term refers to a kind of contagious disease. Journalists and media that have been affected assume that news can give us statements instead of facts. In other words, that the inverted pyramid is licensed to replace verified facts with others opinions. It is time to ask us some questions from an academic perspective. Why is “He said, she said” journalism so rooted on the day-to-day practices of journalists? What are the causes of this strong tendency in the content supply of the media? Have they impacted in the construction of the agenda or in the formation of public opinion? This article tries to give answers to these questions and also suggest to pay attention to a practice that nowadays is considered a necessary evil, although is recognized as a symptom of an insufficient quality of the news that are transmitted by local media.